Health and economic benefits of achieving contraceptive and maternal health targets in Small Island Developing States in the Pacific and Caribbean. Issue 2 (7th February 2023) - Kelly, Sherrie L; Walsh, Tom; Delport, Dominic; ten Brink, Debra; Martin-Hughes, Rowan; Homer, Caroline SE; Butler, Jennifer; Adedeji, Olanike; De Beni, Davide; Maurizio, Federica; Friedman, Howard S; Di Marco, Doretta; et al.
Abstract : Introduction: Reducing unmet need for modern contraception and expanding access to quality maternal health (MH) services are priorities for improving women's health and economic empowerment. To support investment decisions, we estimated the additional cost and expected health and economic benefits of achieving the United Nations targets of zero unmet need for modern contraceptive choices and 95% coverage of MH services by 2030 in select Small Island Developing States. Methods: Five Pacific (Kiribati, Samoa, Solomon Islands, Tonga and Vanuatu) and four Caribbean (Barbados, Guyana, Jamaica and Saint Lucia) countries were considered based on population survey data availability. For each country, the Lives Saved Tool was used to model costs, health outcomes and economic benefits for two scenarios: business-as-usual (BAU) (coverage maintained) and coverage-targets-achieved, which scaled linearly from 2022 (following COVID-19 disruptions) coverage of evidence-based family planning and MH interventions to reach United Nations targets, including modern contraceptive methods and access to complete antenatal, delivery and emergency care. Unintended pregnancies, maternal deaths, stillbirths and newborn deaths averted by the coverage-targets-achieved scenario were converted to workforce, education and social economic benefits; and benefit–cost ratios were calculated. Results: The coverage-targets-achieved scenario required an additional US$12.6M (US$10.8M−US$15.9M) over 2020–2030 for the five Pacific countries (15% more than US$82.4M to maintain BAU). This additional investment was estimated to avert 126 000 (40%) unintended pregnancies, 2200 (28%) stillbirths and 121 (29%) maternal deaths and lead to a 15-fold economic benefit of US$190.6M (US$67.0M−US$304.5M) by 2050. For the four Caribbean countries, an additional US$17.8M (US$15.3M−US$22.4M) was needed to reach the targets (4% more than US$405.4M to maintain BAU). This was estimated to avert 127 000 (23%) unintended pregnancies, 3600 (23%) stillbirths and 221 (25%) maternal deaths and lead to a 24-fold economic benefit of US$426.2M (US$138.6M−US$745.7M) by 2050. Conclusion: Achieving full coverage of contraceptive and MH services in the Pacific and Caribbean is likely to have a high return on investment.